Fashions of a decade. The 1920s - Herald, Jacqueline; Price, Robert (New York : Facts on File, 1991)
Surveys the fads, fashions, trends, and cultural and intellectual preoccupations of the comfortable, high-living 1920s.
Includes bibliographical references (p. 61) and index.
Book Links (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
7-9
Young Adult
Keywords: Civilization, Modern -- 20th century -- Juvenile literature; Costume -- History -- 20th century -- Juvenile literature; Fashion -- History -- 20th century -- Juvenile literature; Civilization, Modern -- 20th century; Costume -- History -- 20th century; Fashion -- History -- 20th century; Costume -- History; Fashion -- History; Modern civilization